(untitled) (Revista Psicología y Sociedad, 2025)
Are we paying too high a price for the convenience and entertainment digital worlds offer? The proliferation of virtual platforms has transformed ways of interacting, learning, and spending leisure time. However, constant immersion in digital environments can affect mental health, particularly in adolescents. Exposure to unfiltered content, the creation of digital identities, and difficulty in differentiating boundaries between the physical and virtual worlds are factors that influence the emergence of psychological issues. It is necessary to analyze the mechanisms through which technology affects emotional well-being and to propose strategies aimed at reducing the risks associated with its use.